KUALITAS VISUM ET REPERTUM PERLUKAAN DI RSUD SELASIH KABUPATEN PELALAWAN PERIODE 1 JANUARI 2009 - 31 DESEMBER 2013 - Sofistiawan, Taufik; Afandi, Dedi; Mursali, Laode Burhannudin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTGood quality is necessary given the crucial role in the proceedings of a criminal offense. Approximately 50-70 percent of cases that come to the Pelalawan Selasih General Hospital during the Period from January 1 2009-31 December 2013 were an injury cases and require a Visum et Repertum (VeR) and usually requested by investigators as evidence. This study was conducted to obtain a VeR quality at the Pelalawan Selasih General Hospital during the period from January 1 2009-31 December 2013. In order to achieve the intended objectives, retrospective descriptive approach has been used in this observational study. All VeR data that match to the inclusion criteria were sampled as many as 288 injury. Herkutanto scoring method is used to analyze 13 elements. The results of this study showed that 66 percent of survivors (190 cases of injury) is a type of highest violence in the age group 22-40 years male sex. 93.8 percent (270 cases) of the highest hardness is a result of blunt force. Quality introduction Ver were classified Good (76 percent). While the main and Conclusions section of each classified Medium (64 percent and 75 percent). The result of quality VeR in Pelalawan Selasih Gneeral Hospital is 50%. Based on these findings it can be concluded that in general the quality VeR injury in the Pelalawan Selasih General Hospital during the period from January 1 2009-31 December 2013 were categorized Medium.Keywords: Visum et Repertum, injury, quality of VeR of injury